An investigation of the effect of smoking, alcohol, and drug use on male infertility - Iswanto, A. Heri; Karim, Yasir Salam; Islam, Md. Zahidul; Alkadir, Ola Kamal A.; Jalil, Abduladheem Turki; Khlaif, Ali T.; Mustafa, Yasser Fakri; Kzar, Hamzah H.; Al-Gazally, Moaed E.; Beheshtizadeh, Narmin (Vesnu Publications, 2022)
Background: Infertility in men has increased in recent years. Numerous physical, chemical, biological, and social factors are known to play a role in reducing semen quality, in between, there are high-risk behaviors that affect the quality of semen. In this paper, the effects of three factors: smoking, alcohol consumption, and drugs have been investigated.